Experimental co-infection of calves with SARS-CoV-2 Delta and Omicron variants of concern - Konner Cool; Natasha N. Gaudreault; Jessie D. Trujillo; Igor Morozov; Chester D. McDowell; Dashzeveg Bold; Taeyong Kwon; Velmurugan Balaraman; Patricia Assato; Daniel W. Madden; Emily Mantlo; Jayme Souza-Neto; et al. (Emerging Microbes and Infections)
Since emerging in late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has repeatedly crossed the species barrier with natural infections reported in various domestic and wild animal species. The emergence and global spread of SARS-CoV-2 variants of concern (VOCs) has expanded the range of susceptible host species. Previous experimental infection studies in cattle using Wuhan-like SARS-CoV-2 isolates suggested that cattle were not likely amplifying hosts for SARS-CoV-2. However, SARS-CoV-2 sero- and RNA-positive cattle have since been identified in Europe, India, and Africa. Here, we investigated the susceptibility and transmission of the Delta and Omicron SARS-CoV-2 VOCs in cattle. Eight Holstein calves were co-infected orally and intranasally with a mixed inoculum of SARS-CoV-2 VOCs Delta and Omicron BA.2. Twenty-four hours post-challenge, two sentinel calves were introduced to evaluate virus transmission. The co-infection resulted in a high proportion of calves shedding SARS-CoV-2 RNA at 1- and 2-days post-challenge (DPC). Extensive tissue distribution of SARS-CoV-2 RNA was observed at 3 and 7 DPC and infectious virus was recovered from two calves at 3 DPC. Next-generation sequencing revealed that only the SARS-CoV-2 Delta variant was detected in clinical samples and tissues. Similar to previous experimental infection studies in cattle, we observed only limited seroconversion and no clear evidence of transmission to sentinel calves. Together, our findings suggest that cattle are more permissive to infection with SARS-CoV-2 Delta than Omicron BA.2 and Wuhan-like isolates but, in the absence of horizontal transmission, are not likely to be reservoir hosts for currently circulating SARS-CoV-2 variants.